Subaxial Cervical Vertebra Pedicle Anatomy: A Radiological Morphometric Study - Saygi Uygur; Irmak Tekeli Barut; Efekan Doruk; Furkan Basar; Yakup Yildirim; Derya Karatas; Emel Avci; Ahmet Dagtekin (Neurological Sciences and Neurophysiology)
Aim: This radiological morphometric study aimed to investigate the morphometry of the pedicles of subaxial cervical vertebrae (C3–C7) and emphasize the importance of preoperative planning to prevent complications during spinal surgery. Materials and Methods: Computed tomography scans of the subaxial cervical vertebrae of 40 patients without cervical pathology were morphometrically evaluated. Key parameters such as pedicle height, pedicle width, pedicle length, pedicle axial angle, pedicle sagittal angle, and vertebral foramen diameter were measured at each vertebral level (C3–C7). Statistical analysis was performed to identify morphometric differences based on individual vertebral levels and patient demographics, particularly between male and female populations. Results: The study revealed significant variations in the pedicle morphometry between different cervical vertebral levels and between sexes. Notably, the C3 vertebrae exhibited the narrowest pedicles, and female patients had consistently smaller pedicle dimensions than male patients. The pedicle axial and sagittal angles also demonstrated substantial variability, with a decreasing trend from C4 to C7. These variations suggest a high degree of anatomical heterogeneity in the subaxial cervical spine. Discussion: The morphometric differences in subaxial cervical vertebrae, particularly between sexes and individual and vertebral levels, highlight the significance of individualized preoperative planning. Thorough radiological assessment of pedicle anatomy is essential for tailoring surgical approaches and reducing the risk of complications such as neurovascular injury due to pedicle screw misplacement. Conclusion: Our findings underscore the critical need for patient-specific preoperative planning to enhance the accuracy of pedicle screw placement and minimize surgical risks in the subaxial cervical spine.